MUC504 : Theory and analysis / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course exposes students to the musical functions of horizontal and vertical relationships of sound organisation in 19th - 21st century works. Students are expected to analyse musical structures and concepts of selected musical excerpts. In addition, students are required to demonstrate autonomous learning in music theory and analysis.